1983
DOI: 10.1001/archderm.119.1.27
|View full text |Cite
|
Sign up to set email alerts
|

12% lactate lotion for the treatment of xerosis. A double-blind clinical evaluation

Abstract: Sixty patients with moderate to severe xerosis participated in a 21-day, randomized, double-blind, contralateral study for efficacy of a specially neutralized 12% lactate lotion compared with a 5% lactic acid lotion and a nonlactated emollient lotion. The severity of xerosis was evaluated on days 0, 7, 14, and 21 during treatment and on days 28 and 35 one and two weeks after treatment was discontinued. All three preparations significantly reduced the severity scores of xerosis. During the "regression" period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previous studies have reported low lactic acid levels in atopic dermatitis patients, 47) and that the topical application of lactic acid was effective for the improvement of xerosis. 48) In healthy individuals, the levels of lactic acid in the stratum corneum are positively correlated with skin hydration and negatively correlated with skin surface pH. 49) Lactic acid is one of the major components of NMFs, which participate in the maintenance of the water content of the stratum corneum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported low lactic acid levels in atopic dermatitis patients, 47) and that the topical application of lactic acid was effective for the improvement of xerosis. 48) In healthy individuals, the levels of lactic acid in the stratum corneum are positively correlated with skin hydration and negatively correlated with skin surface pH. 49) Lactic acid is one of the major components of NMFs, which participate in the maintenance of the water content of the stratum corneum.…”
Section: Discussionmentioning
confidence: 99%
“…10 Lactic acid formed from pyruvic acid in physiological conditions, in aqueous solutions, is one of the most efficient natural factors moisturizing the human skin. 11 These compounds remain in balance with each other as shown in Diagram 1. Due to deprotonation of the hydroxyl group of a-hydroxy acid (AHA), a carbonyl group (ketonic) is created as a result of oxidation leading to an increase in molecular lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the vehicle that contains water, it is converted into lactic acid that possesses the ability to keep water in the epidermis. 10,11 This acid, used in a proper concentration, strongly enhances the synthesis of collagen, elastin, and glycoproteins at the level of the dermis. 12 A favorable feature of the pyruvic peel is its good penetration to sebaceous-hair follicles owing to a very small molecule of 220.66 A.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Pyruvic acid (CH 3 -CO-COOH) is an alpha-keto acid that is converted under physiological conditions to the corresponding alpha-hydroxyacid, lactic acid, one of the most effective natural humectants for human skin. 12 Pyruvic acid has potential as a unique topical peeling agent, combining the keratolytic action of an alpha-keto acid and the humectant effects of lactic acid. The aim of our study was to evaluate the efficacy and tolerability of peeling with pyruvic acid in a group of patients affected by mild to moderate papulo-pustular acne.…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvic acid (CH 3 –CO–COOH) is an alpha‐keto acid that is converted under physiological conditions to the corresponding alpha‐hydroxyacid, lactic acid, one of the most effective natural humectants for human skin 12 . Pyruvic acid has potential as a unique topical peeling agent, combining the keratolytic action of an alpha‐keto acid and the humectant effects of lactic acid.…”
Section: Introductionmentioning
confidence: 99%